A study of caesar cipher and transposition cipher in jawi messages - Mohd Lokman, Syiham; Chuah, Chai Wen; Ab. Rahman, Nurul Hidayah Binti; A. Hamid, Isredza Rahmi Binti (American Scientific Publishers, 2018)
Cryptography known as art and science which is used to hide the messages that contain a few policy terminologies. These terminologies in cryptography are plaintext/ messages, ciphertext, encryption, decryption and key. Encryption is a proses to transform the plaintext together with key into ciphertext. Decryption is the reverse process of encryption. Caesar cipher and transposition cipher are two historical ciphers in cryptography. Caesar cipher is a monoalphabetic cipher. It is a substitution cipher which replace each letter in plaintext with another letter to form the ciphertext. Transposition cipher uses a technique which rearrangement letters in plaintext with a keyword and produce the ciphertext. Caesar cipher and Tansposition cipher both are commonly used to encrypt the English letters. The output of encrypted of English letters are known as ciphertext. The attacker can easily cryptanalysed the Caesar cipher by observing the frequency distribution English letters and ciphertext. For Transposition cipher, the cipher can be cracked by knowing the keyword. To date, there is no any research encrypt Jawi letters using Caesar cipher and Transposition cipher. Hence, in this paper encryption and decryption by using Caesar cipher and Transposition cipher in Jawi messages are proposed. Next, the security level of Caesar cipher and Transposition cipher in Jawi messages are compared. The result has shown that both ciphers are still not secure to protect the confidentiality of the Jawi messages.